Tinjauan Yuridis Terhadap Pengelolaan Sampah di Pondok Pesantren Al-Luqmaniyyah - Madarina Madarina (Supremasi Hukum: Jurnal Kajian Ilmu Hukum, 2019)
Garbage is a problem that is currently being a bywordin various local and long-distance media. Indonesia is evenreferred as the second largest contributor of plastic waste in theworld after China. Yogyakarta is a city with a variety ofinteresting tourist destinations as well as known as studentcities. Many migrants come and stay temporarily inYogyakarta. This has implications for the number ofmushrooming Islamic boarding schools. The number of Islamicboarding schools is of course directly proportional to theamount of waste generated. The relationship with waste,actually there has been a Yogyakarta City Regulation Number10 of 2012 which regulates Waste Management. However, theproblem is that the majority of pesantren residents aremigrants who are likely not aware of this regulation. Thisproblem which is discussed in this paper.